2009
DOI: 10.1021/jm900302q
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Intrinsic Clearance-Based Optimization of N3-Phenylpyrazinones as Corticotropin-Releasing Factor-1 (CRF1) Receptor Antagonists

Abstract: A series of pyrazinone-based heterocycles was identified as potent and orally active corticotropin-releasing factor-1 (CRF(1)) receptor antagonists. Selected compounds proved efficacious in an anxiety model in rats; however, pharmacokinetic properties were not optimal. In this article, we describe an in vitro intrinsic clearance-based approach to the optimization of pyrazinone-based CRF(1) receptor antagonists wherein sites of metabolism were identified by incubation with human liver microsomes. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Further SAR studies on this series, directed at replacing or removing the metabolically labile methoxy groups, led them to BMS-665053 78 (142), a compound that had a 10-fold improvement in rat iv clearance. 79 Additional metabolite ID studies on 142 revealed that the pyrazin-2(1H)-one was susceptible to oxidation and GSH conjugation. 78 The suggested intermediate that led to pyrazin-2(1H)-one metabolism was the chloroepoxide 146, which after hydrolysis or reaction with GSH led to the observed oxidized metabolites 149 and 150 and GSH adducts 147 and 148.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Further SAR studies on this series, directed at replacing or removing the metabolically labile methoxy groups, led them to BMS-665053 78 (142), a compound that had a 10-fold improvement in rat iv clearance. 79 Additional metabolite ID studies on 142 revealed that the pyrazin-2(1H)-one was susceptible to oxidation and GSH conjugation. 78 The suggested intermediate that led to pyrazin-2(1H)-one metabolism was the chloroepoxide 146, which after hydrolysis or reaction with GSH led to the observed oxidized metabolites 149 and 150 and GSH adducts 147 and 148.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…149–150 °C); 54 1 H NMR (400 MHz, DMSO- d 6 , TMS) δ 1.38 (d, J = 6.1 Hz, 3H), 2.22 (s, 3H), 2.73 (dd, J = 16.0, 7.6 Hz, 1H), 3.27 (dd, J = 15.6, 8.9 Hz, 1H), 4.93 (sext, J = 7.0 Hz, 1H), 7.19 (s, 1H), 7.35 (s, 1H), 12.48 (s, 1H).…”
Section: Methodsmentioning
confidence: 99%
“…80–81 °C); 54 1 H NMR (400 MHz, CDCl 3 , TMS) δ 3.11 (t, J = 8.6 Hz, 2H), 3.30 (bs, 2H), 4.48 (t, J = 8.6 Hz, 2H), 6.45 (d, J = 8.2 Hz, 1H), 6.59 (m, 2H).…”
Section: Methodsmentioning
confidence: 99%
“…11 Difluoromethoxy and trifluoromethoxy groups have previously been highlighted as metabolically-stable replacements for methoxy groups. [21][22][23][24] We therefore investigated the effect of the introduction of fluoroalkyl groups into the tranilast structure, while maintaining the acid and double bond functionalities.…”
mentioning
confidence: 99%